Preparation of CeO2 microspheres by internal gelation process with copolymerization using acrylic acid. Issue 9 (15th June 2019) - Ding, Xueqiang; Ma, Jingtao; Zhao, Xingyu; Hao, Shaochang; Li, Ziqiang; Deng, Changsheng; Li, Guanxing
Abstract: Cerium dioxide microspheres were successfully prepared by internal gelation process with copolymerization using acrylic acid. The effects of acrylic acid (AA)/hexamethylenetetramine (HMTA) molar ratio and concentration of solution containing urea and HMTA on the stability of precursor solution and on the prepared microspheres were investigated. The results indicated that acrylic acid could modify the urea resin and slow down the decomposition of urea resin. The stability of precursor solutions was improved with the increase of AA/HMTA molar ratio, but the surfaces of gelled microspheres became rough and cracked when the ratio was greater than 1. The solution containing urea and HMTA had a significant effect on the stability of precursor solution and on the surface morphology, specific surface area, pore volume and average pore diameter of the microspheres. The porous CeO2 microspheres were obtained by heat treatment at 600 °C for 2 h.